The regulation of collective dismissals: Economic rationale and legal practice - Mariya Aleksynska; Angelika Muller (International Labour Organization (ILO), 2020)
This paper offers a legal and an economic analysis of collective dismissals procedures. First, it explains the economic rationale for having collective dismissal procedures in place, in light of the fact that labour markets are not perfect. Second, it overviews the international labour standards pertaining to collective dismissals for economic reasons. Third, using information for 132 countries, it reviews and compares legal practices of collective dismissals throughout the world in the light of the international labour standards. The paper shows that the statutory regulations of collective dismissals are in fact very different from regulations of individual dismissals, not only in the types of the legal procedures that they contain, but also in their economic objectives. The paper also discusses the caveats of making cross-country comparisons of the degree of worker protection, and of the costs to employers, provided by these regulations.
Keywords: 330; employment security; working conditions; conditions of employment; labour contracts; labour law; labour legislation; labour standards